2008
DOI: 10.1080/02688690701827340
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: Can studies of obesity provide the key to understanding pathogenesis?

Abstract: The pathogenesis of idiopathic intracranial hypertension (IIH) is poorly understood. Several mechanisms have been suggested, but no one mechanism has been able to account for all manifestations of the disease. Although IIH predominantly affects obese, premenopausal women, little is known about whether or how the obesity contributes to the IIH. Obesity is a heterogeneous condition, consisting of different phenotypes that are influenced by the regional distribution of adipose tissue. This review explores the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 106 publications
2
50
0
Order By: Relevance
“…In the present study, the obtained results support these facts, whereas in patients with weight loss a better clinical recovery was achieved (Table 4). On the other hand, in our study, approximately a quarter of patients were not obese, which is again similar to the results from the similar IIH series reported by others (27), as our results also correspond to the results from a study testing the relationship between obesity and IIH in a femaleonly population (29,30). Obesity plays a possible role, but it is purely hemodynamic, because the pressure in the venous system is increased due to the increased intraabdominal and intrathoracic pressure.…”
Section: Scientificsupporting
confidence: 82%
“…In the present study, the obtained results support these facts, whereas in patients with weight loss a better clinical recovery was achieved (Table 4). On the other hand, in our study, approximately a quarter of patients were not obese, which is again similar to the results from the similar IIH series reported by others (27), as our results also correspond to the results from a study testing the relationship between obesity and IIH in a femaleonly population (29,30). Obesity plays a possible role, but it is purely hemodynamic, because the pressure in the venous system is increased due to the increased intraabdominal and intrathoracic pressure.…”
Section: Scientificsupporting
confidence: 82%
“…Another study also found significantly lower waist-to-hip ratios in IIH patients compared to obese controls despite the BMI of the IIH group being an average of 7 points higher [60]. Kesler et al [59] contend that these results refute an often cited hypothesis of IIH pathogenesis that intra-abdominal fat increases intra-abdominal pressure, resulting in increased intracranial venous pressure [15,61], since most IIH patients had a higher proportion of lower-body fat versus central obesity. Kesler et al [59] also propose that the prevalence of an estrogenic gynecoid (pear-shaped) fat distribution and the propensity of IIH to affect obese women in their reproductive years support looking further into the role of estrogen in this disease.…”
Section: Adiposity and Obesity Markersmentioning
confidence: 63%
“…It also covers our current knowledge of obesity profiles and markers in IIH. Other recent reviews, including one on pediatric IIH [13] which we published in Hormone Research in Paediatrics in 2010, can provide further scope regarding the multifactorial pathophysiology and treatment options of this disease in adults [14,15] and in children. …”
Section: Introductionmentioning
confidence: 99%
“…33 In keeping with enhanced estrogenicity in the obese, others propose endocrinologic dysregulation leading to a prothrombotic state in obesity and, similarly, in pregnancy, as the pathway that promotes PTC. 34 Other studies note increased leptin levels in obese patients with IIH compared with both obese and nonobese controls, 35 while another group did not find significant differences between leptin levels of patients and controls. 36 A recent study found similar CSF leptin levels in patients with PTC but noted significantly increased CSF levels of the inflammatory cytokine CCL2.…”
Section: Review Articlementioning
confidence: 92%